Comparative microplastic load in two decapod crustaceans Palinurus elephas (Fabricius, 1787) and Nephrops norvegicus (Linnaeus, 1758). (June 2023) - Cau, Alessandro; Gorule, Pankaj A.; Bellodi, Andrea; Carreras-Colom, Ester; Moccia, Davide; Pittura, Lucia; Regoli, Francesco; Follesa, Maria Cristina
Abstract: The present work compares microplastics (MPs) contamination in two charismatic crustaceans: European spiny lobster Palinurus elephas and langoustine Nephrops norvegicus. Samples ( P. elephas n = 14; N. norvegicus n = 15) were collected between 76 and 592 m depth, from four sites in west Sardinia, Italy. An extraction protocol was applied on stomachs and intestines, separately, and over 500 particles were further characterized through μFT-IR. We document 100 % occurrence in specimens from both species, with P. elephas being significantly more contaminated (9.1 ± 1.75 vs. 3.2 ± 0.45 MPs individual −1 ), ingesting larger MPs with different polymeric composition. The scavenging-based feeding strategy of both species could explain such exposure to MPs, mostly derived by single-use plastic. The overall results highlight that both species are clearly affected by plastic pollution, being valuable bioindicators and charismatic species that could thus represent excellent flagship species for raising awareness toward the global issue of plastic in the marine environment. Highlights: We compared microplastic contamination in Palinurus elephas and Nephrops norvegicus . We report 100 % occurrence, polyester and polyethylene as dominant polymers (>65 %). Spiny lobsters ingest more and larger microplastics than langoustines. Langoustines were confirmed to fragment microplastics during digestion. Both species are efficient bioindicators and flagship species of plastic impact.